Radiation-induced changes in DNA methylation and their relationship to chromosome aberrations in nuclear power plant workers - Lee, Younghyun; Kim, Yang Jee; Choi, Young Joo; Lee, Joong Won; Lee, Sunyeong; Cho, Yoon Hee; Chung, Hai Won (International journal of radiation biology, 2015)
Abstract Purpose: We investigated the association between occupational radiation exposure and DNA methylation changes in nuclear power plant workers. We also evaluated whether radiation- induced DNA methylation alterations are associated with chromosome aberrations. Materials and methods: The study population included 170 radiation-exposed workers and 30 controls. We measured global, long interspersed nuclear element-1 (LINE-1), and satellite 2 methylation levels in blood leukocyte DNA. The analysis of chromosome aberrations was performed on peripheral lymphocytes. Results: Global DNA methylation levels were lower in radiation-exposed workers than in controls. The methylation levels were negatively associated with the recent 1.5-year radiation dose in a multiple linear regression model (β = − 0.0088, p ≤ 0.001); the levels increased proportionally with the total cumulative dose in radiation-exposed workers. LINE-1 methylation levels were higher in radiation-exposed workers than in controls and were significantly associated with the total cumulative radiation dose in a multiple linear regression model (β = − 0.031, p = 0.035). Global DNA methylation levels were also correlated with chromosome aberrations among workers. Workers with low global methylation levels had a higher frequency of chromosome aberrations than did subjects with high global methylation levels. Conclusion: Occupational exposure to low-dose radiation could affect DNA methylation levels, and the radiation-induced DNA methylation alterations may be associated with chromosome aberrations.